2014
DOI: 10.1556/jba.3.2014.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences among Internet gaming disorder, gambling disorder and alcohol use disorder: A focus on impulsivity and compulsivity

Abstract: Background and aims: The aim of the present study was to test the impulsivities and compulsivities of behavioral addictions, including Internet gaming disorder (IGD) and gambling disorder (GD), by directly comparing them with alcohol use disorder (AUD) and a healthy control (HC) group. Methods: We enrolled male patients who were diagnosed with IGD, GD or AUD, with 15 patients per group, as well as 15 HCs. Trait impulsivity was measured using the Barratt Impulsiveness Scale version 11 (BIS-11). The stop-signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
119
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 45 publications
(57 reference statements)
11
119
0
1
Order By: Relevance
“…Although some characteristics of impulsive individuals such as deficit in attention, lack of reflection, insensitivity to consequences, delayed reward discounting and inhibition of impulsive responses have a role in addictive behaviors (Crews & Boettiger, 2009;MacKillop et al, 2011) the study of impulsivity can be difficult because researchers use different scales. The three measures most used in the study of impulsivity's role in technological addictions have been those of Dickman (see Collins et al, 2012), Barrat (see Choi et al, 2014;Gentile et al, 2011;Metcalf & Pammer, 2014) and Whiteside and Lynam (see Billieux, 2012;Billieux et al, 2011). Despite the scales' differences, our research suggests that studying the different kinds of impulsivity is useful to understand why MMORPG players are different than other videogame players and to examine the progression from casual to problematic play, in combination with other characteristics such as harmonious and obsessive passion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although some characteristics of impulsive individuals such as deficit in attention, lack of reflection, insensitivity to consequences, delayed reward discounting and inhibition of impulsive responses have a role in addictive behaviors (Crews & Boettiger, 2009;MacKillop et al, 2011) the study of impulsivity can be difficult because researchers use different scales. The three measures most used in the study of impulsivity's role in technological addictions have been those of Dickman (see Collins et al, 2012), Barrat (see Choi et al, 2014;Gentile et al, 2011;Metcalf & Pammer, 2014) and Whiteside and Lynam (see Billieux, 2012;Billieux et al, 2011). Despite the scales' differences, our research suggests that studying the different kinds of impulsivity is useful to understand why MMORPG players are different than other videogame players and to examine the progression from casual to problematic play, in combination with other characteristics such as harmonious and obsessive passion.…”
Section: Discussionmentioning
confidence: 93%
“…In the attempt to understand the player profile, impulsivity has also been studied in relation to videogame play (Choi et al, 2014;Collins et al, 2012;Metcalf & Pammer, 2014). The general theories of impulsivity have to do with the tendency to act without forethought and the negative consequences of that behavior (Eysenck, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies compared the levels of impulsivity in various addictions, but the group of online gamers was younger than the other addicts and the control group (e.g. Choi et al, 2014), which might bias the results. The structure of our sample helped to overcome this problem because it includes a large number of both adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…they were younger, less extroverted, and showed higher levels of social anxiety. In a small clinical sample, Choi et al (2014) found that overall impulsivity was higher in addicted gamers than in both gamblers and a healthy control group. A number of studies also pointed out that online gaming addiction may be influenced by higher levels of sensation seeking (e.g.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation